THE USE OF RECYCLED MATERIALS IN CIVIL ENGINEERING: THE PATH TO SUSTAINABLE CONSTRUCTION - Sutarti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The use of recycled materials in civil engineering is a strategic approach in realizing sustainable construction. This study aims to examine the types, motivations, challenges, and impacts of using recycled materials in construction projects. The research method used was qualitative descriptive with in-depth interview techniques, field observations, and documentation on several urban construction projects that applied recycled materials. The results of the study show that waste concrete aggregates, recycled plastics, fly ash, and glass are the most commonly used materials. Motivations for its use include cost efficiency and encouragement of environmental regulations. However, the main challenge lies in the inconsistent quality of the material and the limitations of its use in the main structure. However, recycled materials have been proven to have a positive impact on environmental aspects and project efficiency, such as reducing carbon emissions, reducing the use of natural materials, and better waste management. These findings show that the use of recycled materials is not only a technical practice, but also an integral strategy in realizing sustainable development. Policy support, technical standardization, and increasing awareness of industry players are the main keys in expanding its implementation.